Effect of Purple Leaf Extract (Graptophyllum Pictum (L.) Griff) on the Number of Macrophage Cells in Pulp Perforation - Devi Eka Juniarti1 , Tuty Kusumaningsih2 , Adioro Soetojo1 , Ninuk Hariyani3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Purple leaf (Graptophyllum pictum (L.) Griff) is one of Indonesia’s traditional medicinal plants, which has anti-inflammatory properties which is expected to stop the inflammation of the pulp accompanied by perforation. Purpose: To determine the effect of giving purple leaves (Graptophyllum pictum (L.) Griff) to the number of macrophage cells in pulp perforation. Method: The study used 24 Wistar rats divided into four groups, namely control (K), and 3 treatment groups P1, P2, P3. Each group consisted of 6 rats prepared, then P1 was given 10% purple leaf extract, P2 was given 15% purple leaf extract, P3 was given 20% purple leaf extract. On the 3rd day, the Wistar rat was sacrificed and continued with the preparation of HPA. Calculation of the number of macrophages was obtained from the One-way ANOVA test. Results: There were significant differences between the control and treatment groups (K with P1, P2, P3), on the results of the One-way ANOVA difference-result test (p <0.05) Conclusion: Purple leaf extract (Graptophyllum pictum (L.) Griff) affected increasing the number of macrophage cells in pulp perforation after the 3rd day of treatment.